Nurses' perceptions of their relationships and communication with lesbian women seeking perinatal care. Issue 17 (29th May 2019) - Tzur‐Peled, Sharona; Sarid, Orly; Kushnir, Talma
Abstract: Aims and objective: To examine whether nurses' assessment of their relationships and communication with lesbian women seeking perinatal care is associated with their personal and professional characteristics and knowledge of homosexuality. Background: Recently, there has been a growing incidence of same‐sex parenthood. Nurses administer health care to lesbian women from pregnancy planning through birth, providing consultation. Although there has been a shift in attitudes towards homosexuality, discrimination is still quite common. Design: This research is part of a larger cross‐sectional study carried out at women's healthcare centres, concerning nurses' perceived quality of perinatal care provided to lesbian women. Methods: The study was conducted from December 2015–April 2016 at women's health centres in Israel encompassing 184 registered nurses who completed self‐report questionnaires. They were assessed as to their knowledge of homosexuality and nurse–patient relationships and communication. The Squire checklist was used. Results: Most (73.4%) had prior acquaintance with lesbian women; only 17.9% had been educated as to lesbian women's unique health needs; of these, 66.7% thought that they had been given professional tools for working with lesbian women; 60.4% were unaware of the importance of knowing the patient's sexual orientation. The average score on a homosexuality knowledge questionnaire was 10.4 on a scale of 0–17, indicating moderate levels of factual knowledge about homosexuality. A significant positive correlation was found between nurses' knowledge of homosexuality and assessment of their relationships and communication with lesbian women seeking perinatal care. In addition, nurses' personal and professional characteristics, such as place of birth, religiosity and familiarity with lesbian women, were related to their assessment of their relationships and communication. Conclusion: Nurses' knowledge of homosexuality and personal and professional characteristics were associated with their perceptions regarding relationships and communication with lesbian women seeking perinatal care. Relevance to clinical practice: Further training might broaden, refine rigid perceptions and contribute to advancing equal perinatal nursing care of lesbian women.